PEDAGOGICAL AND PSYCHOLOGICAL NATURE OF ABILITY - Zilola Dilmurodova (Journal Park Publishing, 2024)
The article analyzes the pedagogical and psychological interpretation of ability.
Keywords: ability, educational process, teacher, student, interest, psychology.